Representation of a Dystopian Society in the novel The City of Ember by Jeanne DuPrau - Rahayu, Eny; Syamsudin, Oom Rohmah (Universitas Indraprasta PGRI, 2023)
This study uses a qualitative descriptive method to describe the representation of a dystopian society and its structure in the novel The City of Ember by Jeanne DuPrau. The aims of this study are (1) to describe a dystopian society that has to adapt to living underground city in the novel The City of Ember by Jeanne DuPrau and (2) to describe the social structure of a dystopian society in the novel The City of Ember. The Structuralism approach is used as the theory approach by focusing on three aspects from Tzvetan Todorov: syntactic aspect, semantic aspect, and verbal aspect. The first data is taken from the novel The City of Ember and the second sources are taken from other supporting books, journals, and articles.